A influência da prática do aleitamento materno na aquisição de hábitos de sucção não nutritivos e prevenção de oclusopatias - Moimaz, Suzely Adas Saliba [UNESP]; Rocha, Najara Barbosa Da [UNESP]; Garbin, Artênio José Isper [UNESP]; Saliba, Orlando [UNESP] (Universidade Estadual Paulista Júlio de Mesquita Filho, 2013)
OBJECTIVE: This study aimed to investigate the relationship between breastfeeding with non-nutritive sucking habits and malocclusion. MATERIAL AND METHOD: The current cross-sectional and retrospective study was performed based on interviews of 330 mothers of children aging from 3 to 6 years old at Araçatuba-SP, after informed consent, using a semi-structured questionnaire that was tested in a pilot study. Clinical examinations were conducted in children (n = 306) in order to evaluated the presence of malocclusion. Two researchers were previously calibrated (Kappa score of 0.91) for interviews and exams assays. Chi-square (χ²) and Fischer's exact test were used to evaluate this relationship at a significant level of 5% (p < .05). Data were processed into the EpiInfo and GraphPad® softwares. RESULT: Most of the mothers (86.4%) breastfed their children; nevertheless, only 33.4% of children were exclusively breastfed up to six months of age. A total of 44% of children had malocclusion, in which 83% of them were not breastfed during the first six months of age. Non-nutritive sucking habits were observed in 53.3% (176) of children, and the baby pacifier was the most prevalent one (31.2%). It was noted a significant association between lack of breastfeeding and presence of: malocclusion (p < 0.001), open bite (p = 0.001), posterior crossbite (p = 0.034), non-nutritive sucking habits (p < 0.001) and pacifier use (p < 0.001). The exclusive lack of breastfeeding was associated with pacifier use (p < 0.001). CONCLUSION: In addition to several advantages, the breastfeeding has an important role in the acquisition of non-nutritive habits and prevalence of malocclusion.

OBJETIVO: Neste estudo, objetivou-se verificar a associação entre prática do aleitamento materno, aquisição de hábitos de sucção não nutritivos e oclusopatias. MATERIAL E MÉTODO: Trata-se de uma pesquisa do tipo transversal, retrospectiva, na qual foram realizadas entrevistas com 330 mães de crianças de 3 a 6 anos de idade de Araçatuba-SP, após consentimento esclarecido, utilizando-se questionário semiestruturado, testado em estudo piloto. Exames clínicos foram realizados nas crianças (n = 306) para verificação de oclusopatias. Dois pesquisadores foram calibrados (Kappa = 0,91) para realização das entrevistas e exames. Os testes Qui-Quadrado (χ²) e Exato de Fischer foram utilizados para verificar associações, em nível de significância de 5% (p < 0,05). Os dados foram processados no programa EpiInfo e GraphPad®. RESULTADO: A maioria das mães (86,4%) amamentou seus filhos, entretanto, apenas 33,4% delas amamentaram exclusivamente no peito até seis meses de vida. As oclusopatias estiveram presentes em 54% das crianças e, entre estas, 83% não foram amamentadas no peito até seis meses de idade. Os hábitos de sucção não nutritivos estiveram presentes em 53,3% (176) das crianças, sendo o uso de chupeta (31,2%), o mais prevalente. Houve associação significante direta entre a falta de aleitamento materno total e as seguintes variáveis: presença de oclusopatias (p < 0,0001); mordida aberta (p = 0,0001); mordida cruzada anterior (p = 0,0346); hábitos de sucção não nutritivos (p < 0,0001), e uso de chupeta (p < 0,0001). A falta de aleitamento materno exclusivo esteve associada com uso de chupeta (p < 0,0001). CONCLUSÃO: O aleitamento materno, além de inúmeras vantagens, exerce papel preventivo na aquisição de hábitos de sucção não nutritivos e na prevalência de oclusopatias.
The effect of breastfeeding in the acquisition of non-nutritive sucking habits and malocclusion prevention
Keywords: Breast feeding; habits; malocclusion; oral health; Aleitamento materno; hábitos; má oclusão; saúde bucal